2017
DOI: 10.12705/664.6
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the phylogeny of the root‐hemiparasitic genus Odontites (tribe Rhinantheae, Orobanchaceae): Evidence for five main lineages

Abstract: Despite the recent publication of several phylogenies focused on Rhinantheae, which has been expanded to include three Asian endemic genera, few studies so far have dealt with particular genera within the tribe. Here, we focus on Odontites and related genera because of the high morphological variability of the group and its unclear generic boundaries. Phylogenetic analyses were performed for nrDNA (ITS) and cpDNA (trnK region and rps16 intron) datasets, using Bayesian and Parsimony analyses. Our results cast d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 44 publications
(70 reference statements)
2
18
0
Order By: Relevance
“…In that chapter, the phylogenetic relationships of the various clades in the family were discussed, and five disconnected phylogenetic trees were shown that included lists of unplaced taxa based on their assumed affinity. Although there have been numerous phylogenetic studies since 2013 (e.g., Schneider & al., ; Uribe‐Convers & Tank, ; Fu & al., ; Pinto‐Carrasco & al., ; Gaudeul & al., ; Yu & al., ; Li & al., ), most have been focused on a particular group (tribe) within Orobanchaceae. It appears that there does not exist in the literature an attempt to incorporate all the available phylogenetic information to produce a “super tree” of Orobanchaceae.…”
Section: Lamialesmentioning
confidence: 98%
See 3 more Smart Citations
“…In that chapter, the phylogenetic relationships of the various clades in the family were discussed, and five disconnected phylogenetic trees were shown that included lists of unplaced taxa based on their assumed affinity. Although there have been numerous phylogenetic studies since 2013 (e.g., Schneider & al., ; Uribe‐Convers & Tank, ; Fu & al., ; Pinto‐Carrasco & al., ; Gaudeul & al., ; Yu & al., ; Li & al., ), most have been focused on a particular group (tribe) within Orobanchaceae. It appears that there does not exist in the literature an attempt to incorporate all the available phylogenetic information to produce a “super tree” of Orobanchaceae.…”
Section: Lamialesmentioning
confidence: 98%
“…A taxonomic solution to the problem of polyphyly in Phtheirospermum was made in Pinto‐Carrasco & al. (), who sunk Ph. muliense C.Y.Wu & D.D.Tao, Ph.…”
Section: Lamialesmentioning
confidence: 99%
See 2 more Smart Citations
“…and Ph. tenuisectum Bureau & Franch., were transferred to Pterygiella based on phylogenetic analyses (Pinto-Carrasco et al 2017). Nevertheless, the monophyly of the genus Pterygiella in traditional sense was also well supported by molecular data (Dong et al 2013, Pinto-Carrasco et al 2017, and if Pinto-Carrasco et al's circumscription is adopted, this genus would be somewhat morphologically heterogeneous and difficult to define.…”
Section: Introductionmentioning
confidence: 96%